The nucleosynthesis of heavy elements in Stars: the key isotope 25Mg - Massimi C.; Koehler P.; Kopecky S.; Mingrone F.; Schillebeeckx P.; Vannini G.; Altstadt S.; Andrzejewski J.; Audouin L.; Barbagallo M.; Bécares V.; Bečvář F.; et al. (EPJ Web of Conferences, 2014)
We have measured the radiative neutron-capture cross section and the total neutron-induced cross section of one of the most important isotopes for the s process, the 25Mg. The measurements have been carried out at the neutron time-of-flight facilities n_TOF at CERN (Switzerland) and GELINA installed at the EC-JRC-IRMM (Belgium). The cross sections as a function of neutron energy have been measured up to approximately 300 keV, covering the energy region of interest to the s process. The data analysis is ongoing and preliminary results show the potential relevance for the s process.